Molecular Study of Toll-Like Receptor 2 Gene of Punganur cattle - Sai Teja; R.K. Chaitanya; K. Lakshmi Kavitha; G. Shushma (The Indian Veterinary Journal, 2026)
Toll-like receptors are type 1 transmembrane proteins expressed in almost all cell types and activate the innate immune system. The present study involved characterization of TLR2 gene of Punganur cattle, a dwarf indigenous cattle breed native to Chittoor district of Andhra Pradesh. The exon 2 of TLR2 gene that contains the entire coding sequence of 2355 bp (784 amino acids) was targeted in two PCR reactions and amplified into two overlapping fragments. Both the specific amplicons are sequenced by Sanger’s method. The nucleotide sequence analysis of TLR 2 gene of Punganur cattle revealed 99.38 per cent identity with the TLR2 sequence of Vechur cattle of Kerala (KT862891; Bos indicus) and 99.9-100 per cent homology with Bos taurus TLR2 sequences (AY 634629, XM 027513488.1) except for the two non-synonymous mutations resulting in animo acid variations Asp63Glu, Ile211Val.